MORPHOLOGIC AND NEUROMOTOR PROFILE ANS ABOUT LIFE STYLE OF PRACTITIONERS OF CIRCUS ARTS (Fiep Bulletin - online, 2014)
The practice of any circus modality demands knowledge of its corporeity and motor ability. Knowledge this developed along of the years of practicing circus activities. The objective of this descriptive work was to propitiate to the Physical Education professionals and students, better information of difficult access that will be important in the process of training prescription for people who practice an atypical or not common physical activity. The sample was composed for ten artists with more than one year of professional practical in Afro Circo of the City of Rio de Janeiro, of both the genders, with age between 15 and 28 years. To analyze the life style, quality of life and physical activity level, was used validated questionnaires. For verification of the physical aptitude levels it was used analysis of corporal composition for anthropometry (ICM, fat percentage and RWH), force tests (dinamometry), push up, abdominal resistance, flexibility (Well's Bank and Flexiteste). The results was ICM and normal RWH, low fat percentage, good and/or excellent abdominal resistance and push up, of manual hold force normal, high flexibility of shoulders, hips and trunk and in accordance with the three used questionnaires, they are, in majority, asset, possess a life style that includes much activity physical and the physical domain is satisfactory.
Keywords: circus; corporal composition; neural motor evaluation